2022
DOI: 10.3390/genes13061022
|View full text |Cite
|
Sign up to set email alerts
|

Near-Hexaploid and Near-Tetraploid Aneuploid Progenies Derived from Backcrossing Tetraploid Parents Hibiscus syriacus × (H. syriacus × H. paramutabilis)

Abstract: Hibiscus syriacus, azalea, is an important woody ornamental shrub planted throughout many temperate and subtropical regions of the world. However, flower size is smaller in this species than some of its relatives. To increase flower size, interspecific hybridization has been used, and such hybrid cultivars are usually characterized by larger flowers, increased vigor, diverse leaf shapes, and reduced fertility. Our earlier studies have shown that these hybrid cultivars could backcross with H. syriacus when used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…In addition, the study’s Arachis tetraploid plants all showed obvious morphological differences. Usually, plants with higher ploidy show significantly different morphologies, including increased leaf and flower sizes [ 15 , 17 , 31 ]. However, the morphological differences are usually not immediately visible in most plant species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study’s Arachis tetraploid plants all showed obvious morphological differences. Usually, plants with higher ploidy show significantly different morphologies, including increased leaf and flower sizes [ 15 , 17 , 31 ]. However, the morphological differences are usually not immediately visible in most plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter internode or more compact plant shapes are commonly observed [52]. However, in some cases, genomedoubled plants show a similar internode length to their original ploidy plant [21,36,53], and some even have longer internodes [42]. Ploidy's impact on growth vigor can vary in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing ploidy frequently results in morphological changes such as "thicker, darker-colored leaves; larger, longer-lasting flowers and thicker petals; enhanced vigor; improved tolerances to environmental stresses, pests, and pathogens; increased metabolite production" [19]. In many ornamental plants, larger flower size was reported to correlate to higher ploidy levels, including Hibiscus [20,21], hybrid Euphorbia [22], Lagerstroemia indica [23], and Impatiens spp. [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation